The Toronto concussion study: a cross-sectional analysis of balance deficits following acute concussion in community-dwelling adults. (16th April 2021) - Sweeny, Michelle; Habib Perez, Olinda; Inness, Elizabeth L.; Danells, Cynthia; Chandra, Tharshini; Foster, Evan; Comper, Paul; Bayley, Mark; Mochizuki, George
ABSTRACT: Objective : To characterize balance deficits in community-dwelling adults following acute concussion. Design: Cross-sectional observational study. Methods: Individuals with acute concussion (n=100) and healthy controls (n=20) completed the BESS (Balance Error Scoring System) and quiet standing trials on forceplates with the eyes open, closed, or during a cognitive dual task. BESS score and centre-of-pressure root mean square and high-frequency power (0.4-3Hz) were used to characterize group differences. In a secondary analysis, participants were subdivided based on self-reported symptoms of balance problems and dizziness using the SCAT-3 (Sport Concussion Assessment Tool – Third Edition) Symptom Checklist. Results: In comparing individuals with concussion and controls, BESS score (16.0 ± 6.0 vs 12.6 ± 3.8; F (1, 116) = 5.814, p = .017) and anteroposterior [ F (1.78, 204.2) = 11.93, p < .001] and mediolateral [ F (1, 114) = 10.05, p = .002] high-frequency power revealed significant group differences. Dividing individuals based on self-reported symptoms revealed significant differences in mediolateral high frequency power, such that participants reporting balance and dizziness problems as well as those participants not reporting balance or dizziness symptoms following concussion were less stable than controls. Conclusions: Deficits in clinical and posturographic measures of balance occur in community-dwelling adults with concussion. These measures do not align with self-reported balance symptoms. Future research and clinical practice aimed at careful selection of optimized balance assessment is recommended.